2021
DOI: 10.1016/j.omto.2021.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Introducing a new reporter gene, membrane-anchored Cypridina luciferase, for multiplex bioluminescence imaging

Abstract: Bioluminescence reporter gene imaging is a robust, high-throughput imaging modality that is useful for tracking cells and monitoring biological processes, both in cell culture and in small animals. We introduced and characterized a novel bioluminescence reporter—membrane-anchored Cypridina luciferase (maCLuc)—paired with a unique vargulin substrate. This luciferase-substrate pair has no cross-reactivity with established d -luciferin- or coelenterazine-based lucifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…67 In 2021, Moroz et al demonstrated quadruple-BLI in vivo with a slightly different approach, using light wavelengthblocked filters to separate signals. 69 They multiplexed RLuc, CBRLuc, CBGLuc, and a new reporter named membraneanchored Cypridina luciferase (maCLuc), which is paired with the vargulin substrate, to visualize a metastatic tumor model.…”
Section: ■ Bli Systems Engineeringmentioning
confidence: 99%
“…67 In 2021, Moroz et al demonstrated quadruple-BLI in vivo with a slightly different approach, using light wavelengthblocked filters to separate signals. 69 They multiplexed RLuc, CBRLuc, CBGLuc, and a new reporter named membraneanchored Cypridina luciferase (maCLuc), which is paired with the vargulin substrate, to visualize a metastatic tumor model.…”
Section: ■ Bli Systems Engineeringmentioning
confidence: 99%
“…A membrane-anchored form of the Gaussia luciferase shows higher signal compared to D-luciferin-based firefly luciferase and coelenterazine-based Renilla and the original Gaussia luciferases in detecting T cells and visualized CAR-T cells targeting tumor [52]. While signals from coelenterazine-based luciferases, including membraneanchored Gaussia luciferase, start to "fade" within a few minutes, firefly luciferase and a recently developed vargulin-based membrane-anchored Cypridina luciferase show stability over 15 min [53]. Multiplex BLI is possible by using different luciferase/substrate combinations.…”
Section: Optical Imagingmentioning
confidence: 96%
“…The most commonly used substrates are D-luciferin (for Firefly luciferase) and coelenterazine (for Renilla luciferase). Vargulin was recently reported for an additional no-cross-reactive substrate with Cypridina luciferase 17 .…”
Section: Introductionmentioning
confidence: 93%